Multimode Fiber Interferometer Based on Graded-Index Polymer CYTOP Fiber - Chapalo, Ivan E.; Theodosiou, Antreas; Kalli, Kyriacos; Kotov, Oleg I. (My University, 2020)
In this article, we present an investigation of a multimode fiber interferometer based on a multimode gradient index perfluorinated polymer fiber. The interferometric response of the polymer fiber was investigated for fiber lengths of 20, 80, and 400 m when fibers were subjected to different perturbation types, such as temperature and strain. The results were theoretically investigated using the averaged characteristics approach and compared with those for silica fiber. Practical features specific to polymer fiber multimode interferometers are discussed. The averaged transfer function was measured and compared with theory at two wavelengths. The influence of fiber length on the interferometer's properties was investigated.
Keywords: Fiber optic sensors; Intermodal interference; Multimode interferometer; Polymer fiber; Specklegram sensors